Common Methods to Treat Addiction in Treatment- Rehabilitation Centers in Tehran - M Sadr; H Emami; S Sigari; R Kharaghani; H Sharifi; MR Masjedi (Tehran University of Medical Sciences, 2012)
Background: This study was to determine common methods to treat addiction used by patients checked into Outpatient Treatment and Rehabilitation Clinics in Tehran.Methods: The study was conducted in Social Security affiliated outpatient clinics including three governmental and several private centers in 22& districts of Tehran. Demographic data, personal information, social characteristics and information regarding prevention, treatment, and follow-up records of 1,372 patients were obtained and analyzed.Results: A majority of cases referring to the treatment centers were male (95.2%).  Patients were 14 to 75 yr (mean 35.48 ± 10.57 yr); 61.7% were married and lived in rented homes in the city; 938/1372 (68.4%) had at least one previous attempt failure when seeking re-treatment. A majority of them (77.8%) had a history of 1 to 4 quit attempts; a number 63.1% had an abstinence period of 1 week to 6 months.Conclusion: The majority of our understudy subjects had a history of previous attempts to treat their addiction with a maximum abstinence period of 6 months.